The effect of corporate social responsibility on earnings management: Bibliometric review - José Manuel Santos-Jaén; Ana León-Gómez; José Serrano-Madrid (International Journal of Financial Studies, 2021)
This review aims to study the knowledge development and research dissemination on the influence of Corporate Social Responsibility (CSR) on earnings management through a social network approach using a bibliometric review. A systematic bibliometric review was carried out on 329 papers obtained from the Clarivate Analytics Web of Science (WoS) Core Collection database. The data were analyzed by year, journal, author, institution, country, affiliation, subject area and term analysis. The results reveal the growing interest of researchers in studying the impact of CSR. Although the USA and China dominate publication production, there are a large number of authors from more than 50 countries around the world. The results also show that being prolific does not imply being influential in this area. The keyword patterns showed some interesting potential areas of study on this topic. The findings of this paper provide insight to the research on the analysis of the influence of CSR on earnings management. The most important findings consist of a number of gaps in the literature, such as gender diversity, voluntary disclosure of information and existence of an audit committee, among others, that allow for future fields of research to improve the analysis of the influence of CSR in EM. This research should also prove helpful to managers, owners and auditors. This is the first bibliometric review developed on this topic and it can be extrapolated to any place in the world.
Keywords: 330; bibliometric review; Corporate Social Responsibility (CSR); earnings management; Web of Science (WoS)